Neuroimaging in acute ischemic stroke: Trends, disparities, and clinical impact. Issue 154 (September 2022) - Wang, Jason J.; Katz, Jeffrey M.; Boltyenkov, Artem; Martinez, Gabriela; O'Hara, Joseph; Gribko, Michele; Pandya, Ankur; Rula, Elizabeth; Sanelli, Pina
Abstract: Introduction: Clinical studies over the past decade expanded the eligibility criteria for endovascular therapy, with advanced imaging selection and new devices leading to higher rates of good outcomes. Herein, we explore the current trends in neuroimaging, associated factors, and impact on treatment and clinical outcomes. Materials and Methods: This is a retrospective study of consecutive acute ischemic stroke patients, admitted to a comprehensive stroke center from 2016 to 2020. Patient characteristics, including age, sex, race, arrival method, admission National Institutes of Health Stroke Scale score and last known well to arrival time; imaging and treatment utilization; and discharge outcome by modified Rankin Scale and disposition were extracted from medical records. Trend and multivariable logistic regression analyses were performed, and trends were stratified by patient characteristics. Results: Of 4, 125 acute ischemic stroke episodes, 15.1% received intravenous thrombolysis only, and 7.5% received endovascular thrombectomy from 2016 to 2020. Neuroimaging utilization trends significantly increased for computed tomography angiography (CTA) (48.7% to 75.2%, p < 0.001) and computed tomography perfusion (CTP) (0.26% to 32.9%, p < 0.001), and decreased for magnetic resonance angiography (MRA) (43.2% to 24.7%, p < 0.001). These trends held after adjusting for patient characteristics. Endovascular thrombectomy and intravenous thrombolysis were significantly more common in patients with CTA and CTP (p < 0.0001), and these treatments were associated with good clinical outcomes after controlling for patient characteristics. Conclusion: We found significantly increased trends in CTA and CTP imaging, which were associated with endovascular thrombectomy and intravenous thrombolysis utilization, in acute ischemic stroke patients from 2016 to 2020.